1995
DOI: 10.1029/94ja02545
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional position and shape of the bow shock and their variation with Alfvénic, sonic and magnetosonic Mach numbers and interplanetary magnetic field orientation

Abstract: A large set of bow shock crossings (i.e., 1392) observed by 17 spacecraft has been used to explore the three-dimensional shape and location of the Earth's bow shock and its dependence on solar wind and interplanetary magnetic field (IMF) conditions. This study investigates deviations from gas dynamic flow models associated with the magnetic terms in the magnetohydrodynamic (MHD) equations. Empirical models predicting the statistical position and shape of the bow shock for arbitrary values of the solar wind pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
287
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(319 citation statements)
references
References 43 publications
30
287
2
Order By: Relevance
“…The latter dimension is in line with results from Peredo et al [1995]. The shape between these two points is approximated with a second-order polynomial function.…”
Section: Modeling and Interpretationsupporting
confidence: 56%
“…The latter dimension is in line with results from Peredo et al [1995]. The shape between these two points is approximated with a second-order polynomial function.…”
Section: Modeling and Interpretationsupporting
confidence: 56%
“…They found that the Earth's bow shock shape is well represented by an eccentric conic when taking into account the variations of the solar wind dynamical pressure. A more extensive study using data from 17 different spacecraft was reported by Peredo et al (1995). This uses a 3-D bow shock shape, and includes the effects of solar wind variations parameterized by the sonic M S , Alfvènic M A and magnetosonic M MS Mach Numbers, as well as the orientation of the IMF direction.…”
Section: Shock Geometrymentioning
confidence: 99%
“…For comparison purposes, we use the Farris et al (1991), Cairns et al (1995), and Slavin and Holzer (1981) models. We do not use the recent Peredo et al (1995) model because it has been shown to overestimate the bow shock stand-off position by as much as 20% (Merka et al, 2003). Table 2 lists the distance from the bow shock along the magnetic field direction and θ Bn0 as obtained from the three bow shock models mentioned above.…”
Section: Shock Geometrymentioning
confidence: 99%
“…The plasma parameter is β ∼ 0.35 with a critical Mach number ∼2.3 (Edmiston and Kennel, 1984). For this set of plasma parameters, the Earth's bow shock positions along the OX and OY axis are expected from observations at ∼(14.8 R E , 29 R E ) respectively (Peredo et al, 1995). The magnetopause is expected around ∼10.6 R E along the nose direction (Peredo, 1995;Merka, 2005).…”
Section: Steady State Magnetospheric: Numerical Stability and Kineticmentioning
confidence: 82%